Bridging the Psychic Distance Through Diaspora Networks: The Case of Polish Firms in Brazil - Aleksandra Wąsowska (Problemy Zarządzania, 2017)
The objective of this paper is to assess the role of Polish diaspora in Brazil as a possible distance-reducing mechanism, facilitating the entry of Polish firms to the Brazilian market. We conclude that the activity of Polish firms in Brazil is very limited, due to a significant psychic distance between the respective countries. A long perceived distance is driven by a number of ‘psychic distance stimuli’ (i.e. geographic, cultural, administrative and economic differences). The psychic distance may be reduced by frequent exposure to a country, however, we conclude that so far, the Polish diaspora in Brazil has not served as a vehicle for such an exposure.